2017
DOI: 10.1007/s10067-017-3554-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite monitoring to guide thiopurine therapy in systemic autoimmune diseases

Abstract: 6-Thioguanine nucleotide (6-TGN) is the active metabolite of thiopurine drugs azathioprine and 6-mercaptopurine. 6-Methylmercaptopurine (6-MMP) is an inactive and potentially hepatotoxic metabolite. A subgroup of patients (shunters) preferentially produce 6-MMP instead of 6-TGN, therefore displaying thiopurine resistance and risk for hepatotoxicity. Outside inflammatory bowel disease literature, few data exist regarding individualized thiopurine therapy based on metabolite monitoring. This study sought to desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 37 publications
0
37
0
1
Order By: Relevance
“…Thiopurine S-methyltransferase activity was tested prior to eliminate a deficiency, which would increase the risk of toxicity. Reactive thiopurine metabolites were monitored to guide therapy dosing and avoid adverse effects due to thiopurine toxicity (targeted 6-thioguanine, levels between 230 and 450 pmol/8 × 10 8 erythrocytes, and 6-methylmercaptopurine, levels <5700 pmol/8 × 10 8 erythrocytes to avoid hepatotoxicity) 8 . The azathioprine dose was progressively increased to 350 mg daily (2.8 mg/kg), respecting these thresholds and under this therapy, his glomerular filtration rate stabilized and his RF and proteinuria remained low (Figure 2); however, he never normalized his C4 and remained PLEX dependent, as evidenced by his recurrent purpura.…”
Section: Case Presentationmentioning
confidence: 99%
“…Thiopurine S-methyltransferase activity was tested prior to eliminate a deficiency, which would increase the risk of toxicity. Reactive thiopurine metabolites were monitored to guide therapy dosing and avoid adverse effects due to thiopurine toxicity (targeted 6-thioguanine, levels between 230 and 450 pmol/8 × 10 8 erythrocytes, and 6-methylmercaptopurine, levels <5700 pmol/8 × 10 8 erythrocytes to avoid hepatotoxicity) 8 . The azathioprine dose was progressively increased to 350 mg daily (2.8 mg/kg), respecting these thresholds and under this therapy, his glomerular filtration rate stabilized and his RF and proteinuria remained low (Figure 2); however, he never normalized his C4 and remained PLEX dependent, as evidenced by his recurrent purpura.…”
Section: Case Presentationmentioning
confidence: 99%
“…Our analysis showed that there was no significant association between 6-MMPR/6-TGN ratio (thresholds of 20 [ 57 ] and 24 [ 82 ]) and liver toxicity (OR 2.9, 95% CI 0.74; 11.55; p = 0.13) ( p = 0.03; I 2 = 80%).…”
Section: Resultsmentioning
confidence: 68%
“…In a pooled analysis of 22 reports [ 40 , 46 , 48 , 56 , 57 , 58 , 65 , 67 , 70 , 72 , 73 , 75 , 84 , 85 , 91 , 92 , 94 , 96 , 98 , 103 , 105 , 107 ], 6-TGN concentrations were significantly higher in patients with leukopenia (mean difference of 127.06 pmol/8 × 10 8 RBC (95% CI 70.88; 183.24; p < 0.01)). We could observe a considerable heterogeneity between studies ( p < 0.01; I 2 = 90%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immerhin geschieht bei einem Drittel der mit Azathioprin behandelten CED-Patienten eine solche Verschiebung des Metabolismus hin zum 6MMP [5]. Daher kann bei ausbleibendem Therapieerfolg oder bei Erhöhung der Transaminasen die Bestimmung der Thiopurinmetabolite im peripheren Blut die weitere Therapie relevant optimieren [6]. So sind 6TGN-Spiegel > 235 pmol/8 × 10 8 Erythrozyten mit einem Therapieerfolg assoziiert, wohingegen 6MMP-Spiegel > 5700 pmol/8 × 10 8 Erythrozyten eine Hepatotoxizität auslösen können (d. h. Hepatotoxizität bei einem Quotienten 6MMP/6TGN > 24) [4].…”
unclassified